2019
DOI: 10.1002/iub.2028
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab inhibits epithelial–mesenchymal transition in prostate cancer by targeting the Akt/YB‐1/AR axis

Abstract: Nimotuzumab is a humanized anti‐EGF monoclonal antibody that has been approved for treating different cancers. However, few studies have examined its therapeutic potential in prostate cancer (PC), a most common and highly aggressive malignancy among male population. We used both LNCaP, and PC3 and PC3‐AR (androgen receptor) cells as the model system and assessed the effects of nimotuzumab on epithelial–mesenchymal transition (EMT) in vitro and in vivo. The EMT makers were detected by immunohistochemistry, qRT‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Small molecules, which is composed about 75% of the anticancer FDAapproved drugs, have an extended history of using as drugs for the treatment of many diseases including diabetes, hypertension, infections, heart failure, rhinitis and cancers. 8,9 Previous study reported a novel peptide, ADH-1, that inhibit Ncadherin (a marker of EMT) function. 10 Yarom et al 11 showed that ADH-1 was commonly well tolerated up to a dose of 1000 mg/m 2 when administered every three weeks in patients with incurable solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules, which is composed about 75% of the anticancer FDAapproved drugs, have an extended history of using as drugs for the treatment of many diseases including diabetes, hypertension, infections, heart failure, rhinitis and cancers. 8,9 Previous study reported a novel peptide, ADH-1, that inhibit Ncadherin (a marker of EMT) function. 10 Yarom et al 11 showed that ADH-1 was commonly well tolerated up to a dose of 1000 mg/m 2 when administered every three weeks in patients with incurable solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…AKT regulates many cellular functions, including growth, proliferation, and survival. A previous study suggested that both EGFR and AKT are upstream signaling activators of YB-1 [ 18 ] and are essential for controlling YB-1 activation in breast cancer [ 31 , 32 ]. In melanoma cells, the MAPK and PI3K/AKT signaling pathways activate and increase YB-1 phosphorylation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that other mechanisms, including epigenetic regulation, are also involved in YB‐1 overexpression. Actually, several signal transduction pathways, such as Akt, ERK, and ribosomal S6 kinase (RSK), as well as transcription factors, such as Twist1, were shown to regulate YB‐1 expression in prostate cancer 9,11‐14 . Collectively, both genetic and epigenetic mechanisms are considered to contribute to YB‐1 overexpression in CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] As a molecular mechanism, YB-1 was indicated to regulate AR and AR variant expressions, leading to progression to CRPC. 7,11,12 Furthermore, YB-1 expression was correlated with AR expression in ADT-naïve prostate cancer. 7 Consistently, YB-1 expression was increased in highly malignant tumors and associated with poor prognosis.…”
mentioning
confidence: 90%
See 1 more Smart Citation